Factors Affecting Tomato Productivity in Western Oromia, Ethiopia: Evidence from Smallholder Farmers - Kifle Degefa; Getachew Biru; Galmesa Abebe (Food, Agriculture and Natural Resources - NETWORKS, 2022)
Tomato is one of the most important fruit vegetable crops in Ethiopia supporting the livelihood and improving the economic life of many farmers. However, the productivity of the crop is low due to poor production management practices, limitations in the availability of pesticides and fungicides, limitations to access information, market fluctuation, and shelf life of the crop. The study was undertaken in western Oromia to understand major factors affecting the tomato productivity of smallholder farmers. It was based on the cross-sectional data collected from 135 randomly selected farmers during the 2019/20 cropping season. The data were analyzed using descriptive statistics and an econometric model. The result depicted that the productivity of tomatoes was significantly affected by inputs like labor, oxen power, fertilizer, and pesticides. From the OLS result, gender, education, family size, off/non-farm activities, farm experience, livestock holding, extension access, credit access, and market/traders information positively affected tomato productivity, while age and field distance was affected negatively. The variety and biotic factors affected the tomato productivity of smallholder farmers positively and negatively, respectively. The findings will be helpful for tomato producers, private companies, and other sectors that participated in crop production by solving the above important variables.